2015
DOI: 10.1371/journal.pntd.0004193
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Schistosoma mansoni and Hookworm Infection Intensities on Anaemia in Ugandan Villages

Abstract: BackgroundThe association of anaemia with intestinal schistosomiasis and hookworm infections are poorly explored in populations that are not limited to children or pregnant women.MethodsWe sampled 1,832 individuals aged 5–90 years from 30 communities in Mayuge District, Uganda. Demographic, village, and parasitological data were collected. Infection risk factors were compared in ordinal logistic regressions. Anaemia and infection intensities were analyzed in multilevel models, and population attributable fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 51 publications
5
46
0
1
Order By: Relevance
“…In the present study, peak hookworm infection was recorded in participants of age 35–39 years. This result was in line with reports from Northwest Ethiopia [23], Southern Ethiopia [22], Uganda [15] and Nigeria [20, 32, 33]. Persistence of hookworms with age might be attributed to ignorance of foot wear among the adult agrarian males [20].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the present study, peak hookworm infection was recorded in participants of age 35–39 years. This result was in line with reports from Northwest Ethiopia [23], Southern Ethiopia [22], Uganda [15] and Nigeria [20, 32, 33]. Persistence of hookworms with age might be attributed to ignorance of foot wear among the adult agrarian males [20].…”
Section: Discussionsupporting
confidence: 90%
“…For instance, hookworm infection cause anaemia by increasing blood and iron loss in the intestinal tract [15]. Some other species such as Ascaris lumbricoides, Entamoeba histolytica, Trichuris trichiura, Strongyloides stercoralis and Giardia lamblia have also been found to have great effect on nutritional status due to increased metabolic rate, anorexia and diarrhoea [15, 16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has further been shown that S. mansoni infections contribute to the burden of anaemia among schoolchildren in endemic areas [59]. Although our earlier study in the study area could not associate Schistosoma mansoni infections with anaemia [34], we assessed the comparative implication of single-dose and repeated-dose Praziquantel treatments on the burden of anaemia among study participants.…”
Section: Discussionmentioning
confidence: 95%
“…mansoni not well studied [12,13,14]. There have been very limited studies on the impact of Schistosome infections on anaemia and undernutrition [8,15,16,17,18]. Further, the few available studies have produced contradicting findings.…”
Section: Introductionmentioning
confidence: 99%